Simulacija razvoja v prostoru zaradi vpliva graditve avtoceste - Bačnar, Damjana (Urbani izziv, 2002)
The procedure for planning highways entails evaluation of possibilities the purpose being selection of the optimal one. In the procedure certain criteria are applied, amongst other evaluation of influences on regional and urban development. Despite the set criteria the chosen route is often contrary to development goals of cities and wider areas - regions, which it affects. The article presents possibilities of using models of effects of highways on settlement development for forecasting consequences of construction. The modelis based on knowledge of effects of already built highways, examples of analysed highway exits are shown with settlement growth. Spatial models are useful tools for forecasting physical changes and simulating effects of projects on physical development or its particular elements.
Keywords: avtoceste; bivalno okolje; gradnja; kvaliteta življenja; naselja; poselitev; raba tal; regionalni razvoj; urbani razvoj; vplivi